A review on indirect coal liquefaction residue used in asphalt pavement. (18th January 2023) - Wang, Zhe; Ji, Jie; Wang, Zihao; Ma, Tong; Li, Pengfei; Han, Bingye; Xu, Xinqiang
Highlights: This synthesis reviewed the current research progress of ICLR in asphalt mixture. ICLR can be developed as fine aggregate to produce asphalt mixture and improve its performances. The current research focuses on the conventional performance of ICIR asphalt mixture. It is necessary to control and recommend reasonable substitution amount and particle size. It is essential to study mechanical and fatigue properties of ICLR ICIR asphalt mixture. Abstract: Indirect coal liquefaction residue (ICLR) is a by-product of coal-to-liquid technology that cannot be avoided in the process of converting raw coal to liquid fuel, causing potential threats to the environment and physical health. In this paper, the global research status of ICLR in asphalt pavement is summarized to promote the further application of ICLR in this field. Firstly, the properties of DCLR are introduced, including physical and chemical properties. Secondly, the current status of comprehensive utilization of ICLR and the research progress of its usage in asphalt pavement is summarized, including the particle size, amount of addition, and its effect on the performance of asphalt mortar and mixture. Finally, the article concludes that the future studies of ICLR should focus on controlling the added particle size and content, clarifying the effect of ICLR's particle size and amount on the mixture's performance, and proposing the rational use index of ICLR. It is necessary to study the working performance and mechanical behavior of ICLR asphalt mixture, especially the research on modulus and fatigue performance needs to be further deepened.